Osobennosti funkcional'nogo obespechenija sorevnovatel'noj dejatel'nosti sportsmenov vysokoj kvalifikacii,specializirujushhihsja v sportivnyh tancah - Soronovich, I.; Rozhkova, T.; Boiko, O. (Science in Olympic Sport, 2018)
Objective. To analyze specific working capacity of elite dancers on the basis of studying the relationship between the aspects of the functional bases and specifics of competitive activity. Methods. Analysis and generalization of literature data, practical experience of top experts, pedagogical observation, peda-gogical testing, expert assessments, respiratory gas analysis, biochemical blood tests, remote heart rate monitoring, methods of mathematical statistics. Results. The differences in levels of specific working capacity between dancers was shown to affect the competitive performance. A high stable heart rate, variations in the dynamics of pulmonary ventilation, aerobic and anaerobic energy supply for exercise show that it is necessary to take into account the aspects of specific physical preparation, which characterize changes in the functional bases of specific working capacity during the entire period of competitive dance performance. This requires to use in the system of specific physical preparation for dancers the training means focused on increasing the speed of activation the energy supply systems and the stability of aerobic energy supply, the ability to use the anaerobic reserve as efficiently as possible throughout the entire period of competitive dance performance. The given data indicate that the efficiency of the energy supply for high-intensity work of variable nature in competitive dance is an important part of demonstration of tech-nical mastery and emotional expressiveness of dancesport. Nevertheless, the data presented clearly show that the capacity measures of the energy supply systems characterize only one aspect of the functional preparedness of the dancers. Conclusions. Particular attention must be paid to the choice of training regimen focused on increasing the efficiency of the respiratory system, in particular, on reducing the respiratory rate during and immediately after dance performance. This is an important factor in the aesthetic perception of the dancer`s specific work and significantly affects the evaluation of the competitive dance performance.